Identification of Peat Swamp Water Gastropods in Sontang Village Bonai Darussalam District Rokan Hulu Regency - Linda Rostiana; Eddiwan Eddiwan; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTPeat swamp waters in Sontang Village have experienced land-use changes, due to logging and forest burning activities, which are feared, will affect the type of Gastropods that live in the peat swamp habitat. This study aims to identify gastropods that live in peat swamp waters in Sontang Village. This research was conducted in April-May 2019, in the sampling areas 1, II and III. Sampling is done once a week for 1 month. The identification of Gastropod samples follows the identification of Rao (1989). The results of the study illustrate that the number of Gastropods caught was 102 individuals, from 2 species namely Belamya sp., As many as 32 individuals and as many as 70 individuals Pomacea canaliculata. Morphometric  Pomacea canaliculata (Snail Mas)  is  a  shell height  ranging  from  17-54.5  mm, shell  width of   about 8.81-49.2  mm,  aperture length of 4.45-29 mm, aperture width of 8-38.5 mm, and length insides range from 10.4 to 40 mm. While the Javanese Tutut type (Belamya sp.) Has morphometric: the height of the shell ranges from 7.41-28.82 mm,  the  width of the shell ranges from 8.56-21 mm, the aperture length of 3.94-10.25 mm, the aperture width of 4.75 -13.08 mm and length of the range of 6.73-18.31 mm. From the results of this study, Pomacea canaliculata is more commonly found and has a larger size than other types. Keywords: Gastropoda, Ampullariidae, Vivivaridae, Peat Swamp.